Terbang Buhun: The Trance Phenomenon among Generation Z in Majalaya - Anngi Lestari Paja (LPPM Institut Seni Indonesia Padangpanjang, 2025)
The Trance phenomenon in the Terbang Buhun Majalaya performance is an event or incident that is often performed among the people of the Majalaya region, precisely in West Java. Trance is always presented in two presentations, namely natural or real trance and trance with a scenario. Terbang Buhun Majalaya has a fairly long artistic historical value and has evolved over time, this art has changed in function and the ebb and flow of this art varies in each region but is still preserved by continuing to use the Terbang musical instrument. The scene of possession or trance with the phenomenon or form of presentation of the scenario or real or natural trance. The problem studied in the research is How is the Terbang Buhun Majalaya Performance Formed at the Walahir Kiansantang Heritage Studio and How is the Trance Phenomenon in Terbang Buhun Majalaya. The research uses a qualitative method with a descriptive and phenomenological approach with the aim of understanding and describing the Form of Performance and knowing the Trance Phenomenon descriptively. Data was obtained through observation, interviews, and validated by experimental trance, then analyzed using the stages of data collection, data reduction, data presentation and drawing conclusions about the Trance Phenomenon that occurred from the original narratives of trance practitioners among Gen Z.